The promotion of cooperative sector as a mitigating driver against poverty and unemployment to enhance Southern Africa’s economic growth and development - Maoto, M. K. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The issue of cooperatives has fascinated a lot of consideration in academic world and industry circle both countrywide and across the globe including Southern Africa as a continent. Africa has been going through difficult times where it faces the challenge of poverty and unemployment. The challenges have had an enormous consequence on the quality of social, cultural and political wellbeing of the nation. This has caused development to run at a very sluggish pace in the past years. This article endeavours to review the literature on the promotion of cooperative sector as a driver towards poverty and unemployment mitigation in Southern Africa. Again, this article aimed at assessing the contribution made by the cooperative sector towards Southern Africa’s economic growth and development. The cooperative sector is acknowledged to be a foremost role player in contributing towards poverty and unemployment reduction and also contribute towards the improvement of economic growth and development. The promotion of cooperative sector is predominantly concentrated on the European and American continent while Southern African continent is given less attention. This issue still needs more investigation, particularly in Southern Africa. The review is based on books, peer reviewed articles, conference papers and chapters in books between the year 2000 and 2016. This paper initiates debate on ways to improve cooperatives sector, their survival rate and escalate their level of competitiveness in Southern African and global market. Despite the contribution which cooperative sector made towards economic growth and development, it still faces several challenges that prohibit them to prosper. Among others, constraints include the following: shortage of critical skills among cooperative members, inadequate access to finance as well as markets, nonexistence of intensive care and appraisal for cooperative improvement. These challenges cause cooperatives to remain vulnerable and weak. The promotion of cooperative sector across Southern African countries could be good start to mitigate poverty and unemployment which will lead to economic growth and development. This article will add value and contribute to cooperative sector literature from an African perspective and also the fact that the cooperative skills form an integral part of SMMEs and large businesses. The article concludes by supporting the notion that cooperative skills are more crucial and should be developed on a wider basis of Africa.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Cooperative sector; Poverty reduction; Unemployment; Economic growth; Economic development; Intergovernmental cooperation; Economic development; Poverty; Unemployment